1342. TOSCANA: The Observational Seroepidemiologic Study of COVID-19 at the United States Naval Academy. (4th December 2021) - Millar, Eugene; Laing, Eric; Saperstein, Adam; Modi, Jitu; Heaney, Christopher; Fraser, Jamie; Shaikh, Saira; Pollett, Simon; Broder, Christopher C; Burgess, Timothy; Coles, Christian L
Abstract: Background: University students, including those at military service academies, are at increased risk of acute respiratory infection (ARI), including SAR-CoV-2, due to crowded living conditions, frequent social interaction and other factors that facilitate pathogen transmission. Unlike many universities, the United States Naval Academy (USNA) continued in-person instruction in Fall 2020 in the midst of the COVID-19 pandemic. The Observational Seroepidemiologic Study of COVID-19 at the United States Naval Academy (TOSCANA, ) a longitudinal cohort characterizes the burden and risk factors of SARS-CoV-2 in USNA midshipmen. Methods: Midshipmen were enrolled August- October 2020. Participants were queried about their ARI risk factors, COVID-19 history, and recent receipt of medical care for any ARI at enrollment, in December 2020 and again in May 2021. Subjects were also asked to provide blood and saliva samples to assess their SARS-CoV-2 serostatus at the same three timepoints. A saliva sample was collected by a subset of subjects in February 2021. Presence of anti-SARS-CoV-2 serum IgG in dried blood spots and saliva was measured by multiplex magnetic microparticle-based immunoassays. Results: 181 midshipmen consented to the study and completed the baseline survey (Table 1). 17 (17.5%) of the 97 subjects who submitted baseline blood sample were SARS-CoV-2 seropositive. Only 4 (24%) positive individuals reported having been tested for or diagnosed with COVID-19 prior to arrival at USNA. 121 participants completed the midyear survey, of whom 61 (50%) submitted a blood sample. 16 (26%) of the midyear specimens were SARS-CoV-2 positive. Of these, 3 were new infections. 73 subjects completed the May survey, and 63 (100%) of the submitted blood samples were positive. 83 subjects provided baseline saliva samples, and 55 submitted saliva at each successive time point. 1 (5%) was positive at enrollment, 9 (17%) were positive at midyear and 47 (96%) were positive in May. Table 1. Key characteristics of TOSCANA participants Conclusion: SAR-CoV-2 prevalence in a sample of USNA midshipmen was < 20% at enrollment. A small proportion of subjects seroconverted between the September and December visits. SARS-CoV-2 positivity rose in May, following a COVID-19 outbreak in February and COVID-19 vaccination efforts in March at USNA. Disclosures: Jitu Modi, MD, GSK (Speaker's Bureau)